Metabolic dysfunction-associated steaotic liver disease self-management among the Hispanic/Latino population - Naomi Hematillake; Mary A. Garza; Mary A. Garza; Emanuel Alcala; Muhammad Y. Sheikh (Frontiers in Public Health)
IntroductionHispanic/Latino populations in the U.S. have the highest prevalence of Metabolic Dysfunction-Associated Steaotic Liver Disease (MASLD), and diet and exercise management are crucial for controlling the disease. While quantitative research on general diet and physical activity within this population exists, studies specifically addressing the quantitative analysis of self-management behaviors in Hispanic/Latino individuals with MASLD are notably scarce. This gap underscores the need for our focused investigation into these specific behaviors under the framework of self-management.ObjectivesOur study aims to investigate how various factors such as age, gender, socioeconomic status, and cultural influences are associated with diet and exercise self-management behaviors in Hispanic/Latino individuals with MASLD. We specifically explore the impact of these demographic and cultural factors as independent variables on the dependent variables of diet and exercise self-management behaviors.MethodsThis study involved 94 participants who were recruited from the Fresno Clinical Research Center to participate in a cross-sectional analysis designed to explore diet and exercise self-management behaviors among Hispanic/Latino people with MASLD. Data were collected from January 2023 to February 2023 using a 54-item Qualtrics survey.ResultsThe average age of the participants was 53 years. Among the participants, 68.1% self- identified as female, and 80.9% had an annual income of at least $35,000. Age b = 0.074, p ≤ 0.001, gender b = 1.242, p ≤ 0.05, and financial stress b = 1.887 p ≤ 0.01 were predictors for poor exercise self-management behaviors. Disease-related knowledge b = −2.264 p ≤ 0.001, and familism b = −0.344 p ≤ 0.05 were predictors for healthy exercise self-management behaviors. There were no significant predictors for diet self-management behaviors among the variables observed in this study.ConclusionAge, gender, and financial stress predicted poor exercise self-management behaviors, while disease-related knowledge and familism predicted healthy exercise self-management behaviors.